Retrograde signals from mitochondria reprogramme skoto-morphogenesis in Arabidopsis thaliana via alternative oxidase 1a. (22nd June 2020) - Merendino, Livia; Courtois, Florence; Grübler, Björn; Bastien, Olivier; Straetmanns, Vera; Chevalier, Fabien; Lerbs-Mache, Silva; Lurin, Claire; Pfannschmidt, Thomas
Abstract : The early steps in germination and development of angiosperm seedlings often occur in the dark, inducing a special developmental programme called skoto-morphogenesis. Under these conditions photosynthesis cannot work and all energetic requirements must be fulfilled by mitochondrial metabolization of storage energies. Here, we report the physiological impact of mitochondrial dysfunctions on the skoto-morphogenic programme by using the Arabidopsis rpoTmp mutant. This mutant is defective in the T7-phage-type organellar RNA polymerase shared by plastids and mitochondria. Lack of this enzyme causes a mitochondrial dysfunction resulting in a strongly reduced mitochondrial respiratory chain and a compensatory upregulation of the alternative-oxidase (AOX)-dependent respiration. Surprisingly, the mutant exhibits a triple-response-like phenotype with a twisted apical hook and a shortened hypocotyl. Highly similar phenotypes were detected in other respiration mutants ( rug3 and atphb3) and in WT seedlings treated with the respiration inhibitor KCN. Further genetic and molecular data suggest that the observed skoto-morphogenic alterations are specifically dependent on the activity of the AOX1a enzyme. Microarray analyses indicated that a retrograde signal from mitochondria activates the ANAC017-dependent pathway which controls the activation of AOX1A transcription. In sum, our analysis identifies AOX as a functional link that couples the formation of a triple-response-like phenotype to mitochondrial dysfunction. This article is part of the theme issue 'Retrograde signalling from endosymbiotic organelles'.